Investment Projects: A different approach of analysis - Andia Valencia, Walter (2010)
This article provides a different conceptual approach on investment projects, considering the flexibility of analysis in different realities of intervention, and incorporating dimensions of study necessary to achieve sustainability of investments in today’s environment.